The prevalence of relapse and its associated factors among smokers attending Klinik Rawatan Keluarga, Hospital Universiti Sains Malaysia. - Norihan , Abu Bakar (2011)
Objectives : To determine the prevalence of relapse and its associated factors among smokers at Klinik Rawatan Keluarga, HUSM. Method : This is a cross sectional study. Two hundred and ninety-four respondents agreed to participate in the study from June until August 2010. The socio-demographic and associated risk factors were recorded in the data questionnaires. Result : A total of 283 respondents managed to complete the questionnaires. There was 96.3% response rate. The proportion of smokers who relapsed was 59.4% (n=168). The significant associated factors to relapse were age less than 40 years old, marital status , Fagerstrom score, duration of smoking and stressful life event. Conclusion: The prevalence of relapsed is high which is comparative to many other studies. For smokers who are attending quit smoking clinics, special attention should be given to those with the associated factors to make our quit smoking clinic more successful.